Effect of the Combination of Vanillin and Chitosan Coating on the Microbial Diversity and Shelf-Life of Refrigerated Turbot (Scophthalmus maximus) Filets - Li, Tingting; Sun, Xiaojia; Chen, Haitao; He, Binbin; Mei, Yongchao; Wang, Dangfeng; Li, Jianrong (Frontiers in Microbiology, 2020)
This study investigated the effect of the combination of vanillin and chitosan (VC) coating on the microbiota composition and shelf-life of turbot fillets (Scophthalmus maximus) during a 15-day storage period at 4±1℃, such as sensory and physicochemical attributes (total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), and pH), and the presence of dominant spoilage microbiota. The results suggested that the sensory and physicochemical quality of turbot fillets effectively improved after treatment with vanillin (final concentration 2.0 mg/mL) combined with 1% chitosan, and the shelf-life was prolonged for 6-7 days, compared with the control group. Furthermore, high-throughput sequencing showed that Proteobacteria (52.2%) and Firmicutes (29.8%) were dominant bacteria at the phylum level in fresh turbot fillets, while Pseudomonadaceae (40.2%) and Lactobacillaceae (39.4%) were dominant bacteria at the family level in deteriorated turbot fillets. However, after VC treatment, the relative abundance of Pseudomonadaceae and Lactobacillaceae decreased significantly due to the growth inhibition of potential bacteria, specifically spoilage bacteria, along with rich bacterial diversity at the end of storage. Therefore, our data indicated that VC treatment might be effective in decreasing bacteria-induced quality deterioration and extending the shelf-life of refrigerated turbot fillets.